PEMANFAATAN SILIKA DARI SEKAM PADI PADA KOMPOSIT POLIESTER TEK JENUH-SILIKA - Yusmaniar Yusmaniar; Maria P. Suryani (Jurnal Riset Sains dan Kimia Terapan, 2017)
Silica was extracted from rice husk ash, and then applied as a filler in Unsaturated polyester/silica(UP/SiO2) composite. The aim of this rpicle were artesearch to know the characteristic of silica and it uses as a filler in composite by tensile strength test. The size variation of silica were 60, 100, 230 and 400 mesh, while variation of silica concentration (% w/w) were 0.5%, 1 %, 1.5 % and 2 %. The analysis concluded that variation of particle size and concentration of silica were reduce the tensile strength of composite Key word: silica, composite, tensile strength